MARKETING INSTRUMENTS TO INFLUENCE CUSTOMERS AS A SALES MANAGEMENT SYSTEM - ZAKHARENKO-SELEZNYOVA, A.; TRAINO, V.; YALOVEGA, N. (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The paper presents the results of research on the use of marketing tools to influence customers on the example of the production and industrial enterprise and improve sales management according to the results of the study. The study is based on the practical application of marketing tools to influence the Limited Liability Company "Storage Modernization System" (LLC "SMS"). Attention is based on marketing tools to influence customers as traditional: exhibitions; Mass media; individual meetings; Excursions and modern Internet marketing: Landing page or standard website, SMM, Media advertising, Teaser advertising, Viral marketing, Emails newsletter. The practical application of all tools of influencing the clients of the company LLC "SMS" is covered in more detail. Attention is based on the use of research by the company on the relationship between the number of customers and the volume of products sold in the dynamics of three years. Using the results of the ABC analysis, further ways to influence customer loyalty with the help of marketing tools of influence are suggested. The formation of consumer loyalty of industrial goods and equipment is considered. It is proved that monthly measurements of the true loyalty index at the enterprise and receiving customer feedback form a positive perception of the company LLC "SMS" by future customers. The program of attraction of new clients is developed, the first result is tested and received. It is emphasized that the marketing tools of influence on the clients of SMS LLC require rethinking in the choice of additional tools that need to be directed to the formation of new areas of sales management. It is emphasized that marketing tools to influence the customers of SMS LLC require rethinking in the choice of additional tools that need to be directed to the formation of new areas of sales management.